1994
DOI: 10.1002/ajh.2830470116
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous factor IX administration to patients with hemophilia B

Abstract: equilibrium between the h/A3 genes is "back lit" by a strong selective force originating approximately 400 generations ago.The "reconstructed' location of the h-allele remarkably corresponds to the calculation that in 400 generations a biological fitness 1% greater than average would produce a change in frequency of the gene for adult lactase persistence from 0.05 (in lactase intolerant populations) to 0.60 in tolerant populations [ 121. Prior to the domestication of animals and the invention of dairying, lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
1
5
1
Order By: Relevance
“…Cheung et al 26 built on the studies of Heimark et al 27 and Stern et al 28 to document that FIX binds to type IV collagen via lysine at position 5 or valine at position 10, identifying the mechanism of extravascular and endothelial binding of hFIX. 26,29,30 The published data [23][24][25] and this report support the hypothesis that FIX can traverse not only from the extravascular space to the systemic circulation but also from the systemic circulation to the extravascular space. Whether or not FIX in the extravascular space has a function For personal use only.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Cheung et al 26 built on the studies of Heimark et al 27 and Stern et al 28 to document that FIX binds to type IV collagen via lysine at position 5 or valine at position 10, identifying the mechanism of extravascular and endothelial binding of hFIX. 26,29,30 The published data [23][24][25] and this report support the hypothesis that FIX can traverse not only from the extravascular space to the systemic circulation but also from the systemic circulation to the extravascular space. Whether or not FIX in the extravascular space has a function For personal use only.…”
Section: Discussionsupporting
confidence: 73%
“…A series of studies that administer the FIX protein subcutaneously have been reported in animals and humans with dosing that ranges from 15 to 200 IU/kg. [23][24][25] All these studies detected measurable FIX in the recipient's plasma following subcutaneous administration. In the study by Liles et al, 25 a single adult patient with hemophilia B (cross-reacting material negative, CRMϪ) given a high-purity plasma-derived hFIX subcutaneously developed a transient, low titer inhibitor (1-2 Bethesda units) months after the clinical study while being treated for a traumatic bleed.…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous FIX has also demonstrated prophylactic efficacy during long‐term treatment in tolerized hemophilic dogs [7]. Application in humans has only occasionally been reported [8,9] and rigorous clinical trials have not been performed, probably because concerns exist that subcutaneous administration of FIX, a neoantigen in patients with hemophilia B, could increase its immunogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma FIX:C levels obtained in the SC group were markedly lower than that in the IV group. The low levels observed in the SC group might be attributed to slow and inefficient transport of FIX protein into the plasma compartment, and protein degradation and FIX clearance at the administration site [22,23]. In the IP group, the obtained levels were relatively higher than those of the SC group, but significantly lower than those of the IV group.…”
Section: Discussionmentioning
confidence: 82%